Effect of sintering temperature on microstructure and mechanical properties of zirconia-toughened alumina machinable dental ceramics. Issue 4 (March 2017) - Fan, Jiangyuan; Lin, Tingting; Hu, Fangxuan; Yu, Yi; Ibrahim, Muhammad; Zheng, Ruibin; Huang, Shengbin; Ma, Jianfeng
Abstract: This study investigated the effect of sintering temperature on the microstructure and mechanical properties of dental zirconia-toughened alumina (ZTA) machinable ceramics. Six groups of gelcast ZTA ceramic samples sintered at temperatures between 1100 °C and 1450 °C were prepared. The microstructure was investigated by mercury intrusion porosimetry (MIP), X-ray diffraction (XRD), and scanning electron microscopy (SEM) techniques. The mechanical properties were characterized by flexural strength, fracture toughness, Vickers hardness, and machinability. Overall, with increasing temperature, the relative density, flexural strength, fracture toughness, and Vickers hardness values increased and more tetragonal ZrO2 transformed into monoclinic ZrO2 ; on the other hand, the porosity and pore size decreased. Significantly lower brittleness indexes were observed in groups sintered below 1300 °C, and the lowest values were observed at 1200 °C. The highest flexural strength and fracture toughness of ceramics reached 348.27 MPa and 5.23 MPa m 1/2 when sintered at 1450 °C, respectively. By considering the various properties of gelcast ZTA that varied with the sintering temperature, the optimal temperature for excellent machinability was determined to be approximately 1200–1250 °C, and in this range, a low brittleness index and moderate strength of 0.74–1.19 µm −1/2 and 46.89–120.15 MPa, respectively, were realized.